A decentred assessment of the impact of 'informal governance' on democratic legitimacy. (January 2022) - Ayres, Sarah
The aim of this article is to examine the impact of informal governance on democratic legitimacy. It draws on the literatures on informal governance and decentred theory to examine how governance mechanisms that are un-written, un-codified and non-institutional impact on democratic legitimacy in governance networks. Drawing on a case study of English devolution in the United Kingdom, this article explores how informal governance impacts on different dimensions of legitimacy – input, throughout and output . It does so by drawing on the narratives and stories of central government officials directly involved in English devolution between 2015 and 2018. Findings reveal that even when formal structures are weak, democratic legitimacy can be secured, especially in promoting effective decision making and problem solving – throughput legitimacy. Nonetheless, a decentred analysis has shown a high level of selectivity and differentiation in central-local relationships that undermine legitimation based on input (inclusiveness) and outcome (results) legitimacy. This assessment provides important new insights into how governance networks characterized by high levels of informality can promote democratic legitimacy in ways that reflect the nuances of political decision making in highly complex environments. The challenge for politicians and policy makers moving forward is to actively manage the inevitable trade-offs generated through the use of informality if accusations of a democratic deficit are to be averted.